Determinação da concentração alveolar mínima (CAM) do sevofluorano em catetos (Tayassu tajacu) - Morais, Alessandro Magno Lustosa de (2013)
Inhaled anesthesia is a widely used technique in the different domestic animal species; however it is little studied in wild animals. The aim of this study was to determine the minimum alveolar concentration (MAC) of sevoflurane (SEVO) in peccaries (Tayassu tajacu), investigate its effects on physiological (heart and respiratory rates, temperature and blood pressure) and blood gas analysis as long as the quality of anesthesia recovery time. Ten adult male peccaries weighting 22.4 ± 1.31 kg were used. MAC determination was obtained through intentional motor response evaluated after supramaximal noxious stimuli by clamping the interdigital space. A positive or negative response to the stimulus was recorded, and ET SEVO then increased (if positive response) or decreased (if negative response) by 10%. Individual MAC was the average of multiple determinations. Physiological parameters and blood gas analysis at different times (before induction of anesthesia, to a concentration of 6%, after MAC determination, at MAC, and after extubation 1.5 MAC) were analyzed by analysis of variance (One Way RM ANOVA) for repeated measures followed by Tukey, the degree of significance of 5% (p <0,05). The MAC of sevoflurane for collared peccaries was determined as 4.26 ± 0.68% with the animals fully recovered at 32,0 ± 9,70 minutes. It was concluded by this study that the MAC for SEVO is similar to recent values reported for pigs, with fully short recovery time, but higher than general values reported for other species